Basal terraces on melting ice shelves - Dutrieux, Pierre; Stewart, Craig; Jenkins, Adrian; Nicholls, Keith W.; Corr, Hugh F. J.; Rignot, Eric; Steffen, Konrad (Geophysical Research Letters, 2014)
Ocean waters melt the margins of Antarctic and Greenland glaciers, and individual glaciers' responses and the integrity of their ice shelves are expected to depend on the spatial distribution of melt. The bases of the ice shelves associated with Pine Island Glacier (West Antarctica) and Petermann Glacier (Greenland) have similar geometries, including kilometer-wide, hundreds-of-meter high channels oriented along and across the direction of ice flow. The channels are enhanced by, and constrain, oceanic melt. New meter-scale observations of basal topography reveal peculiar glaciated landscapes. Channel flanks are not smooth, but are instead stepped, with hundreds-of-meters-wide flat terraces separated by 5-50m high walls. Melting is shown to be modulated by the geometry: constant across each terrace, changing from one terrace to the next, and greatly enhanced on the ∼45° inclined walls. Melting is therefore fundamentally heterogeneous and likely associated with stratification in the ice-ocean boundary layer, challenging current models of ice shelf-ocean interactions. Key Points Basal topography of melting ice shelves is complex Basal terraces appear ubiquitous under melting ice shelves Melting concentrates on walls between terraces.